A DFT study of boron nitride-confined nickel single atoms for the oxidation of methane to methanol. Issue 36 (6th September 2022) - Wang, Sanmei; Yu, Bo; Wang, Liangbing
Abstract : Direct oxidation of methane to methanol (DMTM) remains an economically tantalizing but fundamentally challenging goal because of the highly stable C–H bonds. Embedding Ni into O-doped BN via two N atoms and one O atom coordination (Ni1 /O1 N2 -BN) was an efficient option for DMTM. Abstract : Direct oxidation of methane to methanol (DMTM) remains an economically tantalizing but fundamentally challenging goal because of the highly stable C–H bonds. By using density functional theory calculations, we investigated the catalytic properties of single transition metals (Fe, Pd, Ni) supported on O-doped BN in different coordination environments for DMTM. The results indicated that embedding Ni into O-doped BN via two N atoms and one O atom coordination (Ni1 /O1 N2 -BN) was an efficient option for DMTM. Ni1 /O1 N2 -BN was capable of effectively activating the strong C–H bonds of CH4 by generating key Ni–O intermediates. Besides, Ni1 /O1 N2 -BN also exhibited high selectivity for CH3 OH owing to the inhibition of CH2 competitive species and low desorption energy of CH3 OH. Furthermore, the excellent thermal stability of Ni1 /O1 N2 -BN was verified via ab initio molecular dynamics calculations at 500 K for 10 ps. This work provides a new insight into the fundamental understanding and materials design of high-efficiency catalysts for DMTM.